2023
DOI: 10.3390/plants12030556
|View full text |Cite
|
Sign up to set email alerts
|

Warming Scenarios and Phytophthora cinnamomi Infection in Chestnut (Castanea sativa Mill.)

Abstract: The main threats to chestnut in Europe are climate change and emerging pathogens. Although many works have separately addressed the impacts on chestnut of elevated temperatures and Phytophthora cinnamomi Rands (Pc) infection, none have studied their combined effect. The objectives of this work were to describe the physiology, secondary metabolism and survival of 6-month-old C. sativa seedlings after plants were exposed to ambient temperature, high ambient temperature and heat wave events, and subsequent infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…This is consistent with the optimum temperature for pathogen growth in vitro, which is shown to be around 27 °C [ 49 ]. In a scenario of climate change, with an expected rise in the mean temperature in the following decades [ 69 ], the spread and impact of P. cinnamomi on chestnut stands will most likely increase in Mediterranean areas [ 70 , 71 ]. In contrast, the aggressiveness of P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the optimum temperature for pathogen growth in vitro, which is shown to be around 27 °C [ 49 ]. In a scenario of climate change, with an expected rise in the mean temperature in the following decades [ 69 ], the spread and impact of P. cinnamomi on chestnut stands will most likely increase in Mediterranean areas [ 70 , 71 ]. In contrast, the aggressiveness of P .…”
Section: Discussionmentioning
confidence: 99%
“…This work also highlights the potential for some species to become serious pathogens on sweet chestnut in Mediterranean regions under the current climate change scenario. Climate change, in particular a rise in mean temperatures, extreme precipitation regimes, and severe droughts, could intensify ink disease incidences and further destabilize chestnut stands [ 71 , 76 ]. In the absence of alternative methods to control Phytophthora disease in forests, trunk injection with K-phosphonate remains a valid solution to mitigate the emergence of P. cinnamomi and, overall, reduce the impact of ink disease in chestnut stands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on various species have shown that stress induced by different abiotic and biotic factors can modify the composition of phenolic compounds such as fl avonoids and tannins in different anatomical parts of plants [45]. These secondary metabolites exhibit high antimicrobial activity, are strong inhibitors of digestive proteases, and accumulate mainly in the leaves, stems, and roots of trees [46,47].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…With regard to trees of the genus Quercus, some authors have described the content of phenolic compounds under different abiotic conditions, such as cold and drought [48]. Regarding the response to P. cinnamomi, studies have been conducted on the variations of these compounds in chestnut and their dependence on the temperature of the environment [45].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Compounded by factors linked to global warming, such as environmental shifts, P. cinnamomi incidence is on the rise [ 1 , 5 – 10 ]. Extreme drying and warming temperatures are unfavorable conditions for Phytophthora species and other related subspecies [ 1 , 9 , 11 – 14 ]. To confront this growing threat, new research methodologies are imperative.…”
Section: Introductionmentioning
confidence: 99%